Event studies theory, research, and policy for planned events - Getz, Donald 1949- (Events management series, 2016)
"Event Studies is the only book devoted to developing knowledge and theory about planned events. It focuses on event planning and management, outcomes, the experience of events and the meanings attached to them, the dynamic processes shaping events and why people attend them"--Provide by publisher.